Estudio de factibilidad para la creación de una empresa comercializadora de productos agropecuarios en el cantón El Carmen, Provincia de Manabí. - Aviles Gomez, Sandy Elizabeth (2025)
This project is based on the “Feasibility study for the creation of a company that markets agricultural products in the canton of El Carmen, Province of Manabí, in this case, an investigation was carried out with a quantitative approach of an exploratory and simple descriptive type with a sample of 370 surveys directed at farmers in the canton. In addition, the market study allowed it possible to determine an unsatisfied demand of 1.686.297 units of agricultural products for the first year; In the technical study, it was determined that the annual used capacity will be 18,000. According with the laws and regulations of Ecuador, the company’s name is “AGROCAMPO Marketing of agricultural products S.A”. However, as part of the financial study, an initial investment of $40,637.42 was established, in this case, 57% will be covered by a loan from Banco Loja and the remaining 43% will be own capital, where the retail price will be $14.41. of each product. On the other hand, Through the result of the following indicators: positive VAN (NVP) of $57,031.83; TIR (IRR) of 58.55%; benefit-cost ratio of $1.13 dollars, which means that for every dollar invested, $0.13 cents of profitability will be obtained. The capital recovery period (PCR) will be 2 years, 9 months, and 28 days. As a result, the sensitivity analysis to cost increases and income decreases obtained a value of $0.40 cents, which indicates adequate viability of the project.